2015
DOI: 10.1002/jso.23881
|View full text |Cite
|
Sign up to set email alerts
|

High infiltration of tumor‐associated macrophages is associated with a poor response to chemotherapy and poor prognosis of patients undergoing neoadjuvant chemotherapy for esophageal cancer

Abstract: Infiltration of TAMs, especially M2 macrophages, is associated with a poor response to chemotherapy and poor prognosis of patients with esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 39 publications
8
82
0
Order By: Relevance
“…Thirteen articles evaluated patients’ OS [11, 12, 24, 28, 30-33, 35, 37-40]. The pooled results showed that patients with high level of CD8 + TILs had better OS (pooled HR = 0.68; 95% CI = 0.56-0.84; P < 0.001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen articles evaluated patients’ OS [11, 12, 24, 28, 30-33, 35, 37-40]. The pooled results showed that patients with high level of CD8 + TILs had better OS (pooled HR = 0.68; 95% CI = 0.56-0.84; P < 0.001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 16 articles, including 2121 patients, investigated the prognostic value of CD8 + TILs in patients with EC [11-14, 24, 25, 28, 30-33, 35, 37-40]. Thirteen articles evaluated patients’ OS [11, 12, 24, 28, 30-33, 35, 37-40].…”
Section: Resultsmentioning
confidence: 99%
“…The initiation and progression of esophageal cancer is a complicated process that results from the loss of the normal regulatory pathways controlling cell proliferation, differentiation and apoptosis. However, present therapeutic strategies, including chemotherapy, are characterized by low efficacies (4). Drug resistance and side effects of chemotherapy drugs are major barriers to the success of chemotherapy (5).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-associated macrophages are associated with the EC response to chemotherapy [3]. Sugimura et al [3] have found that filtration of CD68(+) macrophages and CD163(+) macrophages was significantly associated with tumor depth, lymphatic invasion and venous invasion of EC.…”
mentioning
confidence: 99%
“…Sugimura et al [3] have found that filtration of CD68(+) macrophages and CD163(+) macrophages was significantly associated with tumor depth, lymphatic invasion and venous invasion of EC. High infiltration of CD68(+) macrophages and CD163(+) macrophages was significantly associated with poor response to chemotherapy for EC patients undergoing neoadjuvant chemotherapy.…”
mentioning
confidence: 99%